The objective condition ofdevelopment a musical creativity on boundary XX-XXІ of centuries - V.V. Belikova (Academy of Cognitive and Natural Sciences, 2006)
The author approves an idea that musical creativity is the main compound complete system of an culture, accents attention to the objective conditions which are promoting ar not promoting its development on boundary XX-XXI of centuries.